Safe Asset Scarcity and Aggregate Demand - Caballero, Ricardo J.; Farhi, Emmanuel; Gourinchas, Pierre-Olivier (American Economic Review, 2016)
We explore the consequences of safe asset scarcity on aggregate demand in a stylized IS-LM/Mundell Fleming style environment. Acute safe asset scarcity forces the economy into a “safety trap” recession. In the open economy, safe asset scarcity spreads from one country to the other via capital flows, equalizing interest rates. Acute global safe asset scarcity forces the economy into a global safety trap. The exchange rate becomes indeterminate but plays a crucial role in both the distribution and the magnitude of output adjustment across countries. Policies that increase the net supply of safe assets somewhere are output enhancing everywhere.